2018
DOI: 10.1016/j.apcata.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Ni-Cu bimetallic catalysts for hydrogen and carbon nanofilaments production via catalytic decomposition of methane

Abstract: The catalytic decomposition of methane (CDM) is a H 2 production process in which the CO 2 emission of conventional processes is avoided and from which carbon nanofilaments can be obtained as a high added value by-product. In this work, we present a thermogravimetry-based screening of catalysts according to their carbon production in the CDM reaction. Catalysts studied were based on Ni as active phase, using two textural promoters (Al 2 O 3 or MgO) and Cu as dopant element in different proportions: 2.5, 5.0, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 65 publications
7
52
0
Order By: Relevance
“…Moreover, while Ni and Cu tend to form fcc structures at ambient conditions, Co and Fe form hexagonal-close-packed (hcp) and body centered cubic (bcc) structures, respectively. In the case of Cu, a substitutional solid solution (Ni x Cu 1-x ) is formed, consistent with the Vegaard's law [51], which was studied for different Cu concentrations in a previous work [38]. Although Cu increased the lattice constant of the Ni x Cu 1-x crystallites (Ni and Ni"), particles were smaller than those of the undoped catalyst.…”
Section: Characterization Of the Catalystssupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, while Ni and Cu tend to form fcc structures at ambient conditions, Co and Fe form hexagonal-close-packed (hcp) and body centered cubic (bcc) structures, respectively. In the case of Cu, a substitutional solid solution (Ni x Cu 1-x ) is formed, consistent with the Vegaard's law [51], which was studied for different Cu concentrations in a previous work [38]. Although Cu increased the lattice constant of the Ni x Cu 1-x crystallites (Ni and Ni"), particles were smaller than those of the undoped catalyst.…”
Section: Characterization Of the Catalystssupporting
confidence: 80%
“…Recently we reported a thorough comparative evaluation of Cu-doped Ni/MgO and Ni/Al 2 O 3 catalysts studying the influence of Cu loading, textural promoter, CDM operating mode, temperature, and reactor scale on the carbon nanofilaments yield and their resulting final textural and structural properties [38]. Cu modified the Ni x Cu 1−x alloy crystal lattice and its activity, finding different carbon nanofilament growth mechanisms depending on the textural promoter and the Cu loading used in the preparation of each catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the XRD, TEM, and TPR results, it can be concluded that the formed Ni@La2O3/SiO2 catalyst structure cannot only stabilize small nickel particles and reduce carbon accumulation, but also provides more interface between Ni and La2O3. The latter can promote CO2 activation on oxygen vacant sites and on highly basic nature oxygen sites (lanthana oxycarbonates), which was found to be beneficial for inhibiting carbon deposition and enhancing catalytic performance [42,56]. TEM images of the used catalysts are shown in Figure 10.…”
Section: Characterization Of Used Catalystsmentioning
confidence: 99%
“…Carbon nanofibers and encapsulated graphitic carbon were formed over the used Ni-La 2 O 3 /SiO 2 catalyst. Methane decomposes on the nickel surface forming atomic hydrogen and carbon, the latter diffusing to free surface sites on the nickel particle to form graphitic carbon (the graphitic carbon peak is precisely seen in Figure 9) [55,56]. As shown in Figure 10c, Ni particles in the used Ni-La 2 O 3 /SiO 2 catalyst are in the 10-50 nm range, which is much wider than that found in the used Ni@La 2 O 3 /SiO 2 catalyst.…”
Section: Characterization Of Used Catalystsmentioning
confidence: 99%
“…Binary nanoparticles (BNPs) are generally nanosized multi-purpose materials which are used in various applications. In fact, application of these materials can increase the activity and stability of the catalyst, reduce the formation of carbon in the reaction of dry methane reforming, increase the strength of super alloys and fix the shape and sizes of the particles [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%